Penilaian Jasa Wisata Kebun Binatang Bumi Kedaton Resort Di Bandar Lampung Dengan Pendekatan Metode Biaya Perjalanan - Ade Prenada; Samsul Bakri; Susni Herwanti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2017)
Tourism object Bumi Kedaton Resort (BKR) is one of the tourist attractions that can be found in the Province of Lampung and opened to the public in 2009 so that the unknown diversity of attitude necessary for a visitor management strategy from BKR to be able to attract visitors because of competition in the world tourist attractions then increasingly need to give satisfaction to the visitor so that visitors wishing to come back. Therefore need to do research to find out the value of tourist services BKR and economic characteristics of visitors. Economic value of tourism services can be found using the method of travel expenses. The research was carried out in December 2014-February 2015 by doing the interview and questionnaire distributed directly to the respondent as much as 99 people. Sampling of respondents do with inccidental sampling methods respondents who happened to be there on site research with sampling techniques in a non random sampling because not all individuals in the population earn the same opportunities to provide samples. Sampling is done starting at 09:00am-4:00 pm WIB each day and by the time the school holidays, christmas, new year and chinese new year. The results of the determination of the cost of travel of visitors then tested with the method of multiple linear regression using software Minitab 16. The research results showed that travel costs averaged visitors amounted to Rp. 109.176,26/people/visits for all zoning are examined. Calculation based on research data obtained economic values of tourism services BKR is Rp. 24.559.199,69/year. Characteristics that give visitors a real influence against the economic value of tourism services BKR i.e. time visiting when the Sunday school holiday, Chinese new year, christmas and new year, as well as the distance that has value P Value < 0.1. The influence of the dependent variables simultaneously (R-Sq) was 96,6% and R-Sq (adj) is 95,4%. Keywords: Demographic, economic value, tourism services, travel cost.